Definitive treatment patterns and survival in stage II non-small cell lung cancer. (October 2018) - Yan, Sherry X.; Qureshi, Muhammad M.; Suzuki, Kei; Dyer, Michael; Truong, Minh Tam; Litle, Virginia; Mak, Kimberley S.
Highlights: Surgery-based therapy and SBRT for Stage II non-small cell lung cancer are rising. Surgery-based therapy had improved survival compared to non-operative approaches. Chemoradiation & SBRT improved survival over conventionally-fractionated radiation. Abstract: Objectives: This study delineated definitive treatment patterns for Stage II non-small cell lung cancer (NSCLC) in the United States and evaluated survival by treatment approach. Materials and Methods: Patients with clinically-staged Stage II NSCLC treated with surgery-based therapy, chemoradiation, conventionally-fractionated radiation (CFR), or stereotactic body radiotherapy (SBRT) were identified using the National Cancer Database (NCDB). Median survival was estimated using Kaplan-Meier analysis. Crude and adjusted hazard ratios (HR) and 95% confidence intervals were computed using Cox regression modeling. Results: Between 2004–2012, 19, 749 patients met study criteria: 13, 382 (67.8%) underwent surgery-based treatment, 4, 310 (21.8%) received chemoradiation, 1, 606 (8.1%) received CFR, and 451 (2.3%) received SBRT. Surgery and SBRT utilization increased over time while CFR and chemoradiation decreased (all p ≤ 0.002). Patients receiving radiation-based treatments were older, with more comorbidities, and higher T/N stage (all p < 0.0001). With median follow-up of 25.2 months, median survival was 51.6, 23.3, 15.4, and 23.7 months for surgery-based treatment, chemoradiation, CFR, and SBRT, respectively (p < 0.0001). On multivariate analysis, chemoradiation (HR 1.67 [1.59–1.75], p < 0.0001), CFR (HR 2.38 [2.22–2.55], p < 0.0001), and SBRT (HR 1.76 [1.53–2.01], p < 0.0001) were associated with decreased survival versus surgery-based treatment. CFR was associated with decreased survival versus chemoradiation (HR 1.52 [1.41–1.63], p < 0.0001) and SBRT (HR 1.39 [1.19–1.61], p < 0.0001). SBRT was associated with similar survival versus chemoradiation (HR 1.10 [0.95–1.27], p = 0.212). Conclusion: NCDB data demonstrate increasing use of surgery-based treatments and SBRT for Stage II NSCLC over time. Radiation-based therapies were associated with decreased survival compared to surgery. CFR was associated with decreased survival compared to chemoradiation and SBRT.